Volume 1: Aerial Vehicles; Aerospace Control; Alternative Energy; Automotive Control Systems; Battery Systems; Beams and Flexib 2013
DOI: 10.1115/dscc2013-3900
|View full text |Cite
|
Sign up to set email alerts
|

Design of Automotive Control Systems Robust to Hardware Imprecision

Abstract: The hardware used for software implementation on a physical system introduces uncertainty into the controller. If neglected during design, this uncertainty can lead to poor controller performance, resulting in significant design and verification iterations. In this work, the effect of sampling time, quantization, and fixed-point computation are directly accounted for in the control design. Sampling time is compensated for by a discrete-time controller. A generic methodology is developed for modeling the worst-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 0 publications
0
19
0
Order By: Relevance
“…in Eq. (12), and assuming a small enough sampling time (T ), which means all terms that contain T 2 can be neglected, Eq. (12) can be re-arranged as follows:…”
Section: Second Order Discrete Sliding Mode Controlmentioning
confidence: 99%
See 1 more Smart Citation
“…in Eq. (12), and assuming a small enough sampling time (T ), which means all terms that contain T 2 can be neglected, Eq. (12) can be re-arranged as follows:…”
Section: Second Order Discrete Sliding Mode Controlmentioning
confidence: 99%
“…The main reason to add the switching function to the calculated equivalent control input of the SMC is reducing the chattering [6]. As it has been shown in [10,12,13], the addition of the switching function with a fix or variable gain enhances the robustness of the controller against uncertainties, which could overpower the chattering issues. The gain of the switching function (sgn(ξ i (k −1))), which depends on the DSMC tuning parameters (λ, β) and g (Eq.…”
Section: Global Asymptotic Stability Of the 2 Nd Order Dsmcmentioning
confidence: 99%
“…For the first group, results in [3] showed that the robustness of the implemented controller against ADC uncertainties can be improved by incorporating the maximum ADC uncertainty bounds into the controller equations. Converting the controller design from a single-input single-output (SISO) to a multi-input multi-output (MIMO) Figure 1: Background of some previous studies [3,4,5,6,7,8,9,10,11,12,13,14,15,16,17] on SMC design against ADC and modeling uncertainties.…”
Section: Introductionmentioning
confidence: 99%
“…Quasi and baseline discrete sliding mode controllers were introduced and studied under implementation imprecisions in [7] and [8], respectively. The robustness of the DSMC design was enhanced by incorporating the maximum ADC uncertainty bounds on control inputs in [9]. The results showed that the proposed DSMC with maximum ADC uncertainty bounds can lead to better tracking performance in comparison with the baseline SMC/DSMC.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation